2017
DOI: 10.1111/acps.12826
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic (delusional) depression and suicidal attempts: a systematic review and meta‐analysis

Abstract: Despite data inconsistency and clinical heterogeneity, this systematic review and meta-analysis showed that patients with PMD are at a two-fold higher risk, both during lifetime and in acute phase, of committing a suicidal attempt than patients with non-PMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 68 publications
3
31
0
2
Order By: Relevance
“…In addition, Wolfersdorf et al [ 63 ] following the same methodology with the above-mentioned study found only very small and inconclusive numbers of suicide victims. The results of Roose et al’s [ 11 ] study are in line with the findings of our recently published meta-analysis of 20 studies [ 20 ] which found a twofold increase of suicide attempt during the acute phase. The authors of the Roose et al’s [ 11 ] study attempt to answer the question “is the risk for suicide of PMD compared to non-PMD patients increased during a major depressive episode?” We consider this question as the most crucial in clinical practice and their results are alarming at the highest degree.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, Wolfersdorf et al [ 63 ] following the same methodology with the above-mentioned study found only very small and inconclusive numbers of suicide victims. The results of Roose et al’s [ 11 ] study are in line with the findings of our recently published meta-analysis of 20 studies [ 20 ] which found a twofold increase of suicide attempt during the acute phase. The authors of the Roose et al’s [ 11 ] study attempt to answer the question “is the risk for suicide of PMD compared to non-PMD patients increased during a major depressive episode?” We consider this question as the most crucial in clinical practice and their results are alarming at the highest degree.…”
Section: Discussionsupporting
confidence: 87%
“…In the Maj et al [ 19 ] and in the Schneider et al [ 64 ] studies, the numbers of PMD patients with or without mood congruent psychosis who committed suicide are too small to be conclusive. In addition, our recent meta-analysis [ 20 ] on suicidal attempts found the evidence scarce on this topic. Moreover, rather the high prevalence of mixed psychotic features in PMD, 58% in the Burch et al’s [ 72 ] study underlines the restrictions that research work can face to clarify the differential effect of mood congruent vs. mood incongruent psychosis on suicide risk evaluating the two concepts in a categorical way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the risk of SA in patients during current MDD episode was found to be 7.5 times higher than in patients who had fully remitted (Sokero et al ., 2005). Also, psychotic features are associated with a two-fold higher risk of SA during the current depressive episode (Coryell et al ., 1984; Maj et al ., 2007; Gournellis et al ., 2017). Moreover, inpatients usually need hospitalization due to insufficient treatment response, which could further increase the suicide risk in MDD (Souery et al ., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The causes of suicide-related behaviours are complex and associated with biological, sociocultural and clinical factors (Coentre et al ., 2017, Gournellis et al ., 2017, Sudol and Mann, 2017). Common risk factors of SA identified in depressed patients include high level of education, lower quality of life, childhood abuse, family history of psychiatric disorders, hopelessness, negative or stressful life events, psychiatric comorbidities and impulsive and aggressive behaviors (Corruble et al ., 1999; Dumais et al ., 2005; Dervic et al ., 2006; Dieserud et al ., 2010; Zayas et al ., 2010; Hawton et al ., 2013; Zhu et al ., 2013; Nam et al ., 2016; Wei et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%